Application of Biomechanical Analysis of Pencak Silat Techniques - Alan Alfiansyah Putra Karo Karo; Tandiyo Rahayu; Heny Setyawati; Siti Baitul Mukarromah (Universitas Negeri Semarang, 2023)
Pencak silat is a self-defense method with distinctive movements that utilize every part of the human body as a sport. These movements are organized into a set of fundamental techniques, including as blocks, punches, kicks, kicks, punches, drops, and slams, and are known as moves. Based on the foregoing, the researchers' plan for this study is to do biomechanical analyses of the Pencak Silat technique. The method used in this research is scientific journals are reviewed quantitatively in order to provide an overview of the journals' quality, maturity, productivity, and other factors. Journals or scientific publications published between 2019 and 2023 that were retrieved from the Scopus and Sinta databases served as the research data for this study. Using